La Antropología Política en México: un estado de la cuestión - Rodríguez Castillo, Luis (2012)
In this collaboration it made a revision of the scientific literature about power relations in order to show the most influential paradigms in the Mexican Political Anthropology. This work has three objectives: 1) to offer a version of the field of study; 2) to make a critical analysis of the theoretical approaches used; and 3) to establish the relevance of current analysis models used in the field of the Anthropological Sciences for the study of power relations about Mexico.